Relationship Between Diet Patterns and Anemia in Female Adolescents - Setya Widhawati; Suparji Suparji; Tinuk Esti Handayani; Tutiek Herlina (Knowledge Dynamics, 2024)
Background: In the process of becoming a mother, a young woman must prepare herself, especially in meeting nutritional needs to prevent anemia, in order to ensure a quality next generation of the nation. Anemia can cause fatigue, decreased productivity, and disorders in cognitive and motor development in children. This study aims to determine the relationship between diet and the incidence of anemia in young women. Methods: The research design used was cross-sectional to examine the relationship between diet and anemia status. The population in this study were 127 students of grade VII of SMP Negeri 5 Ponorogo, with samples taken using a total sampling of 127 students. The independent variable in this study was diet, while the dependent variable was anemia. The instruments used included questionnaires and hemoglobin (Hb) level examination tools. Data collection was carried out through Hb level screening and filling out questionnaires distributed via Google Form. Data analysis used cross-tabulation and Chi-square test. Results: The results showed that 75.59% of adolescents had good diets, while 24.41% had poor diets. Anemia status showed that 79.53% did not have anemia and 20.47% had anemia. The Chi-square test showed the analysis result p = 0.017, which indicated a significant relationship between diet and the incidence of anemia in adolescent girls. Conclusion: This study shows a significant relationship between diet and the incidence of anemia in adolescent girls. Adolescents with good diets tend to have a lower risk of anemia. It is recommended that adolescent girls continue to maintain a good diet to prevent anemia, which can affect their overall health, including productivity and cognitive development.